Evaluating the Improved Research Capacity of EPSCoR States: R&D Funding and Collaborative Networks in the NSF EPSCoR Program. - Melkers, Julia; Wu, Yonghong (Review of Policy Research, 2009)
States vary considerably in their ability to attract federal research and development (R&D) sources. The National Science Foundation (NSF) Experimental Program to Stimulate Competitive Research (EPSCoR) was created in the late 1970s and was designed to enhance the research capacity of less competitive states in seeking federal research funds. How has EPSCoR improved research capacity in its member states? To date, little evaluation of EPSCoR as a program, or even within individual states, has occurred, and those studies that have been conducted have taken a statewide, macro-level approach. We argue that a social-capital-based approach that addresses capacity development among EPSCoR recipients provides important scientist-level data that can best address capacity development issues. In this article, we first examine the data of federal academic R&D obligations in order to analyze one of the direct outcomes of capacity building. We conduct a descriptive statistical analysis on the changing share of federal academic R&D obligations for individual states in recent years. Second, using an NSF-sponsored survey of scientists in the 50 states, we present data on distinctions between scientists in EPSCoR versus non-EPSCoR states, as well as differences between scientists who have been involved in EPSCoR versus those who have not. From our analysis we find important evidence of capacity development in EPSCoR states. Perhaps most importantly, our results provide an important first step in identifying relevant evaluative issues for EPSCoR.